A composite film with room temperature self-repairing, radiation cooling and mechanical response characteristics and preparation method thereof

By using a composite film of hydrogen bond-containing silicone elastic matrix with silica aerogel particles and cesium tungstate nanoparticles in the mechanical response smart window, the problem of narrow dimming range and inability to recycle is solved, and the problem of Room temperature self-healing, radiation cooling and mechanical response characteristics improve energy saving and cycle stability.

CN119119714BActive Publication Date: 2025-02-14重庆智晶时代科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411621202.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-14
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

Nanocomposite films have problems with narrow dimming range and inability to recycle in mechanically responsive smart window applications.

Method used

A composite film was prepared by a solution casting process using a silicone elastomeric matrix containing hydrogen bonds as the basis of the film, combining silica aerogel particles and cesium tungstate nanoparticles.

Benefits of technology

The composite film has achieved room temperature self-healing, radiation cooling and mechanical response characteristics, improved its visible light transmittance regulation performance and cyclic stability, and has a wide wave regulation effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119714B_ABST
    Figure CN119119714B_ABST
Patent Text Reader

Abstract

The present application discloses a composite film with room temperature self-repairing, radiation cooling and mechanical response characteristics and a preparation method thereof, which belongs to the technical field of intelligent polymer material preparation. The composite film with room temperature self-repairing, radiation cooling and mechanical response characteristics provided by the present application includes: a hydrogen-bonded siloxane elastic matrix and silica aerogel particles and cesium tungstate nanoparticles compounded in the hydrogen-bonded siloxane elastic matrix. The composite film prepared by the present application has excellent room temperature self-repairing, radiation cooling, near-infrared shielding performance and mechanical response characteristics, can achieve the effect of wide-band regulation, and after repeated stretching, its performance in regulating visible light transmittance is not significantly reduced, has excellent cycle stability, and has broad application prospects in energy-saving buildings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of intelligent polymer material preparation, and in particular relates to a composite film having room temperature self-repairing, radiation cooling and mechanical response characteristics and a preparation method thereof. Background Art

[0002] With the development of science and technology, environmental problems are becoming increasingly serious, so the efficient use of energy has received widespread attention. As a dynamic green technology, new energy-saving buildings can adjust their transmittance according to changes in outdoor weather and temperature, thereby reducing the energy consumption required for indoor heating, cooling and lighting, and have gradually become a research hotspot. Multifunctional mechanical response smart windows provide a good platform for the development of energy-saving buildings. For practical applications, there are still some difficulties and challenges. 1) How to construct a wide-band adjustable mechanical response smart window to further improve its energy-saving effect. 2) How to increase its cycle life and recycling to reduce pollution to the environment.

[0003] Therefore, the development of multifunctional mechanically responsive smart windows with self-repair, radiation cooling functions and good cyclic stability has important scientific significance and socio-economic value, and provides important technical support for my country's sustainable development and the achievement of its "dual carbon" goals. Summary of the invention

[0004] The present application discloses a composite film having room temperature self-repairing, radiation cooling and mechanical response characteristics and a preparation method thereof, aiming to solve the technical problems of narrow dimming range and non-recyclability of nano-composite films in mechanical response smart window applications.

[0005] In order to achieve the above purpose, the technical solution of this application is:

[0006] The first aspect of the present application provides a composite film with room temperature self-healing, radiation cooling and mechanical response characteristics, including: a hydrogen-bonded siloxane elastic matrix and silica aerogel particles and cesium tungstate nanoparticles composited in the hydrogen-bonded siloxane elastic matrix.

[0007] The second aspect of the present application provides a method for preparing the composite film having room temperature self-repairing, radiation cooling and mechanical response characteristics as described in the first aspect, the preparation method comprising:

[0008] Adding amino-dicapped polydimethylsiloxane, isophorone diisocyanate and terephthalaldehyde into tetrahydrofuran for reaction, separating and collecting the bottom precipitate to obtain a hydrogen-bonded siloxane elastic matrix;

[0009] The hydrogen-bonded siloxane elastic matrix, silicon dioxide aerogel particles and cesium tungstate nanoparticles are added into tetrahydrofuran and mixed, and a solution casting process is adopted to obtain a composite film with room temperature self-repairing, radiation cooling and mechanical response characteristics.

[0010] In combination with the second aspect, preferably, the amino di-terminated polydimethylsiloxane, isophorone diisocyanate and terephthalaldehyde are added in a molar ratio of 1:0.6-1:0-0.4.

[0011] In combination with the second aspect, preferably, the size of the silica aerogel particles is 300 nm-20 μm.

[0012] In combination with the second aspect, preferably, the mass fraction of the silica aerogel particles is 1-20%.

[0013] In combination with the second aspect, preferably, the size of the cesium tungstate nanoparticles is 20-200 nm.

[0014] In combination with the second aspect, preferably, the mass fraction of the cesium tungstate nanoparticles is 1-5%.

[0015] The third aspect of the present application provides the application of the composite film with room temperature self-repairing, radiative cooling and mechanical response characteristics described in the first aspect or the composite film with room temperature self-repairing, radiative cooling and mechanical response characteristics made by the preparation method described in the second aspect in energy-saving buildings.

[0016] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application include at least:

[0017] The composite film provided by the present application is compounded in the hydrogen-bonded siloxane elastic matrix by silica aerogel particles and cesium tungstate nanoparticles. On the one hand, due to the action of the intermolecular urea group and the reversible imine bond in the film, the composite film exhibits excellent self-healing ability; on the other hand, because silica and the elastic matrix have similar refractive indices, it has excellent visible light transmittance. When stretched, a gap is formed between silica and the elastic matrix, and the refractive index of the air in the gap does not match the refractive index of silica and the elastic matrix, thereby generating scattering to reduce its visible light transmittance. At the same time, after repeated stretching, its performance in regulating visible light transmittance is not significantly reduced, and it has excellent cyclic stability; on the third aspect, the addition of cesium tungstate can make the composite film have good visible light transmittance and near-infrared shielding performance, achieve the effect of wide-band regulation, and will not affect the room temperature self-healing and radiation cooling performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0019] Figure 1 This is a scanning electron microscope image of the silica aerogel particles added in the examples of the present application;

[0020] Figure 2 This is a scanning electron microscope image of cesium tungstate nanoparticles added in the examples of the present application;

[0021] Figure 3 Optical microscope images of the A1-composite film prepared in the embodiment of the present application before and after self-repair;

[0022] Figure 4 The transmission spectra of the A1-composite film prepared in the embodiment of the present application under different strains;

[0023] Figure 5 A stress-strain curve diagram of the A1-composite film prepared in the embodiment of the present application;

[0024] Figure 6 The transmission spectra of the A1-composite film prepared in the embodiment of the present application in the initial state before and after 100 and 1000 cycles;

[0025] Figure 7 This is the emission spectrum of the A1-composite film prepared in the embodiment of the present application in the range of 2.5-20 μm;

[0026] Figure 8 Transmission spectra of B1-composite film, A3-composite film, A4-composite film, A5-composite film, A6-composite film, A7-composite film and A8-composite film prepared in the examples of the present application in the visible light range;

[0027] Fig. 9 The transmission spectra of the A6-composite film prepared in the embodiment of the present application under different strains;

[0028] Fig.10 This is a transmission spectrum of the A6-composite film prepared in the embodiment of the present application in the range of 300-2500 nm;

[0029] Fig.11 Transmission spectra of B4-composite film, A9-composite film, A10-composite film, A1-composite film, A11-composite film and A12-composite film prepared in the examples of the present application in the visible light range;

[0030] Fig.12 This is a scanning electron microscope image of silicon dioxide nanoparticles added in the preparation of the examples of the present application;

[0031] Fig.13 The transmission spectra of the B2-composite film prepared in the embodiment of the present application under different strains;

[0032] Fig.14 This is a transmission spectrum of the B3-composite film prepared in the embodiment of the present application in the range of 300-2500 nm;

[0033] Fig.15 This is an emission spectrum of the B3-composite film prepared in the embodiment of the present application in the range of 2.5-20 μm;

[0034] Fig.16 This is a transmission spectrum diagram of the B5-composite film prepared in the examples of the present application under different strains. DETAILED DESCRIPTION

[0035] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0036] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0037] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0038] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0039] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0040] It should be noted that all raw materials and reagents in the examples of the present application were purchased on the market or prepared according to conventional methods well known to those skilled in the art.

[0041] In a first aspect, an embodiment of the present application provides a composite film having room temperature self-healing, radiation cooling and mechanical response characteristics, comprising: a hydrogen-bonded siloxane elastic matrix and silica aerogel particles and cesium tungstate nanoparticles composited in the hydrogen-bonded siloxane elastic matrix.

[0042] Among them, on the one hand, due to the role of the intermolecular urea group and reversible imine bond in the film, the composite film exhibits excellent self-healing ability; on the other hand, due to the similar refractive index of silica and the elastic matrix, it has excellent visible light transmittance. When stretched, a gap is formed between silica and the elastic matrix, and the refractive index of the air in the gap does not match the refractive index of silica and the elastic matrix, thereby generating scattering to reduce its visible light transmittance. At the same time, after repeated stretching, its performance in regulating visible light transmittance has not been significantly reduced, and it has excellent cyclic stability; thirdly, the addition of cesium tungstate can make the composite film have good visible light transmittance and near-infrared shielding performance, achieve the effect of wide-band regulation, and will not affect the room temperature self-healing and radiation cooling performance.

[0043] In a second aspect, the present application also provides a method for preparing the composite film having room temperature self-repairing, radiation cooling and mechanical response characteristics as described in the first aspect, the preparation method comprising:

[0044] Adding amino-dicapped polydimethylsiloxane, isophorone diisocyanate and terephthalaldehyde into tetrahydrofuran for reaction, separating and collecting the bottom precipitate to obtain a hydrogen-bonded siloxane elastic matrix;

[0045] The hydrogen-bonded siloxane elastic matrix, silicon dioxide aerogel particles and cesium tungstate nanoparticles are added into tetrahydrofuran and mixed, and a solution casting process is adopted to obtain a composite film with room temperature self-repairing, radiation cooling and mechanical response characteristics.

[0046] It should be noted that the present application adopts a solution casting process to make a composite film, by directly casting a polymer solution into a flat mold, waiting for the solvent to evaporate and form a film at an appropriate temperature. This operation method is simple and convenient and suitable for large-scale production. At the same time, the preparation process of the present application is simple and easy to operate, with strong repeatability, and has broad application prospects in mechanical response smart windows.

[0047] It should be noted that terephthalaldehyde plays the role of a chain extender in the reaction. The aldehyde group in the terephthalaldehyde molecule is a highly active reactive functional group, which can react with free radicals, terminal groups or other active groups in the polymer chain to introduce new polymer segments. This reactivity enables terephthalaldehyde to effectively extend the length of the polymer chain and may form a branched structure.

[0048] In the embodiment of the present application, the amino-dicapped polydimethylsiloxane, isophorone diisocyanate and terephthalaldehyde are preferably added in a molar ratio of 1:0.6-1:0-0.4. Among them, amino-dicapped polydimethylsiloxane is a soft segment component of the system, and its mechanical properties can be effectively adjusted by controlling the composition content of the soft segment. The side groups contained in the main chain can effectively adjust the molecular chain spacing in the polymer network, improve the ductility of the molecular chain, and thus improve the mobility of the molecular chain. Isophorone diisocyanate is a hard segment component of the system. If the molar ratio is too high, the rigidity of the elastomer will increase, and if it is too low, the viscosity of the elastomer will increase. Therefore, it is necessary to reasonably control the proportion of raw materials added to generate an elastomer with excellent mechanical properties. At the same time, the elastomer contains a large number of hydrogen bonds and has room temperature self-healing properties.

[0049] In the embodiment of the present application, the size of the silica aerogel particles is preferably 300 nm-20 μm, and the added mass fraction is preferably 1-20%. Among them, by adjusting the size and content of the silica aerogel particles, the film is given excellent dimming properties. When the composite film is in the initial state, since the silica aerogel particles and the polydimethylsiloxane (PDMS) elastic matrix have similar refractive indices (PDMS is about 1.4, SiO 2 1.46), so the composite film has a high visible light transmittance. When the composite film is stretched, gaps will be generated at the interface between the PDMS elastic matrix and the silica aerogel particles. Since the refractive index of the air in the gap (1.0) does not match the refractive index of the PDMS elastic matrix and the silica aerogel particles, scattering occurs, resulting in a decrease in the visible light transmittance of the composite film.

[0050] In the embodiment of the present application, the size of the cesium tungstate nanoparticles is preferably 20-200 nm, and the added mass fraction is preferably 1-5%. Among them, by regulating the size and content of the cesium tungstate nanoparticles, the composite film is given good near-infrared shielding properties, and a high visible light transmittance is maintained, achieving the effect of wide-band regulation.

[0051] The third aspect of the present application provides the application of the composite film with room temperature self-repairing, radiation cooling and mechanical response characteristics described in the first aspect or the composite film with room temperature self-repairing, radiation cooling and mechanical response characteristics prepared by the preparation method described in the second aspect in a mechanical response smart window. Among them, based on the excellent room temperature self-repairing, mechanical response, radiation cooling and cyclic stability characteristics of the above-mentioned composite film, it can be widely used in energy-saving buildings and other fields, and has strong product competitiveness.

[0052] The technical solution of the present application will be further described below in conjunction with specific embodiments.

[0053] Example 1

[0054] This embodiment provides a method for preparing an Al-composite film, which specifically includes:

[0055] S101: 10 g NH 2 -PDMS-NH 2 Dissolve in 30 ml tetrahydrofuran and transfer to a round-bottom flask, add 0.59 g isophorone diisocyanate, react at room temperature for 24 hours under nitrogen atmosphere, dissolve 0.09 g terephthalaldehyde in 5 ml N,N-dimethylformamide, add to the flask and continue to react at room temperature for 24 hours, pour the resulting solution into a large amount of deionized water for washing, and after vigorous stirring, a milky white flocculent precipitate is formed, which is washed three times with deionized water and dried in an oven at 50 °C for 12 hours to obtain an elastic matrix;

[0056] S102: The elastic matrix is ​​dissolved in tetrahydrofuran, 10 wt% of silica aerogel particles and 3 wt% of cesium tungstate nanoparticles are added and ultrasonically dispersed for 5 min. After being magnetically stirred at 200 rpm, the A1-composite film is obtained by solution casting on glass coated with polyvinyl alcohol (PVA).

[0057] In order to verify the appearance morphology of the raw materials used to prepare the composite film in the examples of the present application, the raw materials added in the examples were tested by scanning electron microscopy. The results were as follows: Figure 1-2 As shown; among them, Figure 1 is a scanning electron microscope image of the added silica aerogel particles; Figure 2 This is a scanning electron micrograph of the added cesium tungstate nanoparticles.

[0058] according to Figure 1 As is known, the silica aerogel particles were subjected to scanning electron microscopy tests at different magnifications, as shown in a) and b), and it is obvious that the silica aerogel particles are in the form of nanoparticles and are porous materials with a continuous network structure.

[0059] according to Figure 2 As is known, the cesium tungstate nanoparticles were subjected to scanning electron microscopy tests at different magnifications, as shown in a) and b), and it is obvious that the cesium tungstate nanoparticles also present a nanoparticle structure.

[0060] In order to verify the comprehensive performance of the composite film prepared in the examples of the present application, the composite film prepared in Example 1 was tested for self-healing performance, transmission spectrum, mechanical properties, and infrared emission spectrum. The results are as follows: Figure 3-Figure 7 shown.

[0061] according to Figure 3 From the test results, it can be seen that the optical microscope images of the A1-composite film before and after self-repair were tested, where a) is before cutting; b) is placed at room temperature for 24 hours after cutting. As shown in the figure, the composite film completed self-repair after being placed at room temperature for 24 hours after cutting.

[0062] according to Figure 4 From the test results, it can be seen that the transmission spectrum (300-2500 nm) of the A1-composite film under different strains was tested. After stretching, the A1-composite film can change from a transparent state (~ 61%) to an opaque state (~ 13%) in the visible light range, and the transmittance in the near-infrared region is less than 30%.

[0063] according to Figure 5 From the test results, it can be seen that the stress-strain curve of the A1-composite film was tested, and the maximum strain in the elastic deformation stage was about 25%.

[0064] according to Figure 6 From the test results, it can be seen that the transmission spectrum (300-2500nm) of the initial state of the A1-composite film was tested before and after 100 and 1000 cycles at 20% strain (before cycle: black, 100 cycles: red, 1000 cycles: blue). As shown in the figure, after 100 and 1000 cycles of 20% strain stretching, the transmittance of the composite film in the visible light and near-infrared light range only decreased slightly, and its performance in regulating the visible light transmittance and shielding performance for near-infrared light did not decrease significantly, and it has good cycle stability.

[0065] according to Figure 7 From the test results, it can be seen that the emission spectrum of the A1-composite film in the range of 2.5-20 μm was tested, and it has excellent (> 90%) infrared emissivity in the atmospheric transparent window (8-13 μm).

[0066] Therefore, the A1-composite film prepared in Example 1 of the present application has room temperature self-healing properties and excellent dimming performance. After stretching, it can be transformed from a transparent state (~ 61%) to an opaque state (~ 13%) in the visible light range, and the transmittance in the near-infrared region is less than 30%. It has good cycle stability and radiation cooling function (infrared emissivity > 90%).

[0067] Example 2

[0068] The present embodiment provides a method for preparing an A2-composite film, and the component ratio, preparation operation, and process parameters are basically the same as those in Example 1, except that in the second step of the present embodiment, no cesium tungstate nanoparticles are added, and the mass fraction of the silica aerogel particles is 0%, 1%, 3%, 5%, 8%, 10%, 15%, and 20%, and correspondingly, B1-composite film, A2-composite film, A3-composite film, A4-composite film, A5-composite film, A6-composite film, A7-composite film, and A8-composite film are obtained.

[0069] In order to verify the optimal doping content of silica aerogel particles when preparing the composite film in the embodiment of the present application, the composite film prepared in Example 2 was tested and the results were as follows: Figure 8-Figure 10 shown.

[0070] according to Figure 8 The test results show that when different contents of silica aerogel particles are added, the transmission spectra of B1-composite film, A3-composite film, A4-composite film, A5-composite film, A6-composite film, A7-composite film and A8-composite film in the visible light range are tested. The transmittance of the composite film in the visible light range decreases with the increase of the content of silica aerogel particles. Therefore, the mass fraction of silica aerogel particles is limited to 1-20%.

[0071] according to Fig. 9 The test results show that the transmission spectra (400-800nm) of the A6-composite film under different strains were tested. When the amount of silica aerogel particles added was 10 wt%, after stretching, the transmittance of the film changed from ~78% to ~11%, with a higher contrast and a higher initial transmittance. Therefore, the optimal doping content of silica aerogel particles is 10 wt%.

[0072] according to Fig.10 From the test results, it can be seen that the transmission spectrum of the A6-composite film in the range of 300-2500 nm was tested, and its transmittance in the near-infrared region is very high (> 80%).

[0073] Example 3

[0074] The present embodiment provides a method for preparing an A8-composite film, and the component ratio, preparation operation, and process parameters are basically the same as those in Example 1, except that the amount of cesium tungstate nanoparticles added in this embodiment is 0%, 1%, 2%, 3%, 4%, and 5%, and correspondingly, B4-composite film, A9-composite film, A10-composite film, A1-composite film, A11-composite film, and A12-composite film are obtained.

[0075] In order to verify the optimal doping content of cesium tungstate nanoparticles when preparing the composite film in the embodiment of the present application, the composite film prepared in Example 3 was tested and the results were as follows: Fig.11 shown.

[0076] according to Fig.11 From the test results, it can be seen that by adding 10 wt% silica aerogel particles and different contents of cesium tungstate nanoparticles, the transmission spectra of B4-composite film, A9-composite film, A10-composite film, A1-composite film, A11-composite film and A12-composite film in the range of 300-2500 nm were tested. As shown in the figure, the transmittance of the composite film in the visible light and near-infrared light range decreases with the increase of cesium tungstate nanoparticle content, and the decrease in transmittance in the near-infrared region is very significant.

[0077] When the doping content of cesium tungstate nanoparticles is 3 wt%, the transmittance of the composite film in the visible light range is about 64%, and the transmittance in the near-infrared region is < 30%. Therefore, the optimal doping content of cesium tungstate nanoparticles is 3 wt%.

[0078] At the same time, in order to verify the comprehensive performance of the composite film prepared in the above examples, the present application provides the following comparative examples for detailed description.

[0079] Comparative Example 1

[0080] This comparative example provides a preparation method for a B2-composite film, and the component ratio, preparation operation, and process parameters are basically the same as those in Example 1, except that in this comparative example, the mass fraction of the silicon dioxide nanoparticles is 1%, the size is 300 nm, and no cesium tungstate nanoparticles are added to obtain a B2-composite film.

[0081] according to Fig.12 From the test results, it can be seen that the scanning electron microscope image of silica nanoparticles shows a nano-granular structure.

[0082] according to Fig.13 From the test results, it can be seen that the transmission spectrum (400-800 nm) of the B2-composite film under different strains was tested. In the initial state, the transmittance of the B2-composite film in the visible light range was ~40%, and the transmittance after stretching was about 60%, which is a very poor effect.

[0083] Comparative Example 2

[0084] This comparative example provides a method for preparing a B3-composite film, and the component ratio, preparation operation, and process parameters are basically the same as those in Example 1, except that in the second step of this comparative example, cesium tungstate nanoparticles and silica aerogel particles are not added to obtain a B3-composite film.

[0085] according to Fig.14 From the test results, we can see that the transmission spectrum of B3-composite film in the range of 300-2500 nm was tested. As shown in the figure, the transmittance of B3-composite film is relatively high in the visible light and near-infrared light ranges.

[0086] according to Fig.15 From the test results, it can be seen that the emission spectrum of the B3-composite film in the range of 2.5-20 μm was tested, and it has a very high (> 90%) infrared emissivity in the atmospheric transparent window (8-13 μm).

[0087] Therefore, the B3-composite film prepared in the present application has a transmittance of about 90% in the visible light and near-infrared light range, but has no mechanical response characteristics.

[0088] Comparative Example 3

[0089] This comparative example provides a method for preparing a B5-composite film, which specifically includes:

[0090] The silicone elastomer PDMS and the curing agent (Sylgard 184, Dow Corning) were mixed in a mass ratio of 10:1, and 10wt% silica aerogel particles were added and ultrasonically dispersed for 5 min. After being magnetically stirred at 200 rpm and vacuum degassed, the mixture was spin-coated on glass at a speed of 1000 rpm and then heated in an oven at 100 °C for 2 h to prepare the B5-composite film.

[0091] according to Fig.16 From the test results, it can be seen that the transmission spectrum of the B5-composite film under different strains was tested. After stretching, the B5-composite film changed from a transparent state (~ 60%) to an opaque state (~ 40%) in the visible light range, with low contrast and no self-healing function.

[0092] Therefore, the composite film provided by the present application is prepared by reacting amino-dicapped polydimethylsiloxane, isophorone diisocyanate and terephthalaldehyde to generate a hydrogen-bonded siloxane elastic matrix, and then dispersing silica aerogel particles and cesium tungstate nanoparticles in the hydrogen-bonded siloxane elastomer. The composite film can have excellent room temperature self-repair, radiation cooling, near-infrared shielding performance and mechanical response characteristics, can achieve the effect of wide-band regulation, and after repeated stretching, its performance in regulating visible light transmittance is not significantly reduced, has excellent cycle stability, and has broad application prospects in energy-saving buildings.

[0093] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0094] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.

Claims

1. A composite film with room temperature self-repairing, radiation cooling and mechanical response characteristics, characterized in that: include: A hydrogen-bonded siloxane elastic matrix and silicon dioxide aerogel particles and cesium tungstate nanoparticles compounded in the hydrogen-bonded siloxane elastic matrix; The mass fraction of the silica aerogel particles is 1-20%; The mass fraction of the cesium tungstate nanoparticles is 1-5%.

2. A method for preparing a composite film having room temperature self-repairing, radiation cooling and mechanical response characteristics as claimed in claim 1, characterized in that: The preparation method comprises: Adding amino-dicapped polydimethylsiloxane, isophorone diisocyanate and terephthalaldehyde into tetrahydrofuran for reaction, separating and collecting the bottom precipitate to obtain a hydrogen-bonded siloxane elastic matrix; The hydrogen-bonded siloxane elastic matrix, silicon dioxide aerogel particles and cesium tungstate nanoparticles are added into tetrahydrofuran and mixed, and a solution casting process is adopted to obtain a composite film with room temperature self-repairing, radiation cooling and mechanical response characteristics.

3. The method for preparing a composite film having room temperature self-repairing, radiation cooling and mechanical response characteristics according to claim 2, characterized in that: The added molar ratio of the amino-diblocked polydimethylsiloxane, isophorone diisocyanate and terephthalaldehyde is 1:0.6-1:0-0.4; and the added amount of terephthalaldehyde is not zero.

4. The method for preparing a composite film having room temperature self-repairing, radiation cooling and mechanical response characteristics according to claim 2, characterized in that: The size of the silica aerogel particles is 300 nm-20 μm.

5. The method for preparing a composite film having room temperature self-repairing, radiation cooling and mechanical response characteristics according to claim 2, characterized in that: The size of the cesium tungstate nanoparticles is 20-200 nm.

6. Use of a composite film having room temperature self-repairing, radiative cooling and mechanical response characteristics as claimed in claim 1 or a composite film having room temperature self-repairing, radiative cooling and mechanical response characteristics made by the preparation method of any one of claims 2 to 5 in energy-saving buildings.

Citation Information

Patent Citations

  • Self-repair organosilicon material preparation method

    CN109575291A

  • Self-repairing polysiloxane elastomer and preparation method thereof

    CN114133570A